Foz do Iguaçu - PR na rede de cidades - Conte, Cláudia Heloiza (2012)
The objective of this study was to understand the role played by Foz do Iguaçu - PR at the beginning of the XXI century in the network of cities. To reach it, it was dealt with the genesis and structure of this area, considering four stages of colonization of the city, looking for a comprehension the 1970s considering its economic activities and social relations. To better understand the currently economic activities developed in Foz do Iguaçu, it was necessary to understand the socio-spatial changes that occurred since the 1970s, through the construction of the Itaipu Hydroelectric Plant. It was during this period, combined with a strong economic development process known as "economic miracle", represented by the substitution of imports from state investments, when Foz do Iguaçu and cities around were deeply affected. The transformations affect many aspects of the regional fact, for example a huge population growth, the expansion of infrastructure and agricultural activities, commercial and service providers, as well as the dynamics of relations between cities of the urban network. Supported on IBGE studies (1972, 1987, 1993, 2008), it was possible to understand some aspects of the evolution of the urban network, and identify the actual regional network and the centrality of Foz do Iguaçu. Field researches about different activities in Foz do Iguaçu - trade, services, tourism - besides the qualitative surveys among the cities of Foz do Iguaçu, Ciudad Del'Este and Puerto Iguazu have allowed the comprehension about the insertion of Foz do Iguaçu in different networks. It was found a complex of insertions, where some specific details make of Foz do Iguaçu the most inserted city in three different networks of cities.